2011
DOI: 10.1007/s13277-011-0185-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms involved in folate and methionine metabolism and increased risk of sporadic colorectal adenocarcinoma

Abstract: This pilot study has compared the polymorphic genotype frequencies of methylenetetrahydrofolate reductase (MTHFR A1298C and C677T), methionine synthase (MTR A2756G), methionine synthase reductase (MTRR A66G), and thymidylate synthase (TS 2R/3R) in 113 patients with sporadic colorectal adenocarcinoma (SCA) and 188 healthy blood donors, used as matched controls. The aim was to assess the role of these genotypes in the increased risk of SCA among the southeastern Brazilian population. Carriers of genotype MTRR 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…For the MTHFR A1298C , MTRR A66G , MTR A2756G analyses, 12, 6, and 7 studies were conducted in Caucasians, respectively, while 5, 3, and 3 studies were in Asians. Genotype distributions in the controls of all studies were in HWE except for 8 studies for MTHFR C677T polymorphism 29, 31, 37, 40, 44, 48-50, 4 studies for A1298C polymorphism 14, 17, 28, 41, 1 study for MTRR A66G polymorphism 47, and 1 study for MTR A2756G polymorphism 17. The detailed characteristics of the included studies were shown in the supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For the MTHFR A1298C , MTRR A66G , MTR A2756G analyses, 12, 6, and 7 studies were conducted in Caucasians, respectively, while 5, 3, and 3 studies were in Asians. Genotype distributions in the controls of all studies were in HWE except for 8 studies for MTHFR C677T polymorphism 29, 31, 37, 40, 44, 48-50, 4 studies for A1298C polymorphism 14, 17, 28, 41, 1 study for MTRR A66G polymorphism 47, and 1 study for MTR A2756G polymorphism 17. The detailed characteristics of the included studies were shown in the supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The MTHFR C677T, MTHFR A1298C, and MTR A2756G single nucleotide polymorphisms have been found to alter levels of folate and homocysteine, which changes the functionality of expressed proteins [25]. The MTHFR and MTR genes have been widely studied, and the MTHFR C677T, MTHFR A1298C, and MTR A2756G polymorphisms are associated with risk of several cancers [10,[26][27][28][29][30]. Lopez-Cortes et al found that the MTHFR C677T polymorphism has significant effects on susceptibility to prostate cancer in an Ecuadorian population [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Le Marchand et al (77) observed that the MTHFR 1298C allele was weakly protective against CRC. However, Guimarães et al (69) reported that the carriers of the combined variants MTHFR 1298AC+CC and 677CT+TT exhibited an increased risk of CRC, whether in isolation or in combination. According to Shannon et al (14) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…The conflicting conclusions among the studies mentioned above may be attributed to several causes. First, the sample sizes of the populations included in several studies were relatively small (19,27,69), which may result in false-positive or false-negative outcomes. Second, the eligibility criteria for inclusion of control subjects differed among the studies.…”
Section: Discussionmentioning
confidence: 99%